Factors Affecting Learning Transfer of Staff in Short-Term Training at Sime Darby Group Education Department: A Case Study of ESQ Way 165 - Zainuddin, Ismail (2011)
The transfer of training is a critical issue faced by all organizations. This issue is concerned with the impact of training on employees and the organization. Trainee's characteristics, training design, work environment and motivation to transfer are identified in many studies as the four major factors affecting the transfer of training. This study is aimed at investigating the transfer of training of the EQS Way 165 program organized by the Sime Darby Group Education Department. The objectives of the study were: (1) to determine the level of learning transfer occurred after the ESQ training; (2)to examine relationship between trainee characteristics, motivation to transfer, work environment, training design and acquisition of knowledge and skill, and learning transfer. Forty-five staffs out of 65 participants who attended three separate training programs were interviewed. Data were gathered through personal interviews using questionnaires specifically designed for these studies. Four relationships were tested by using ANOVA and Pearson Correlation Analysis. The findings from the study showed that the level of transfer of training among the participants was rather high. However, the study also found that only gender has a significant impact on transfer of training, while other variables such as age, tenure, work environment (supervisor, peer and organizational support), motivation to transfer and training design did not have a significant relationship with transfer of training.